(x - 3)(x+3) - (x - 2)^3 = 1
Tìm x giúp mình với
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Để hệ vô nghiệm thì
\(\dfrac{2m-1}{m+3}\ne\dfrac{5}{1}\\ \Leftrightarrow2m-1\ne5\left(m+3\right)\\ \Leftrightarrow m\ne-\dfrac{16}{3}\)
\(\dfrac{2m-1}{m+3}=\dfrac{3}{-4}\left(m\ne-3\right)\\ \Leftrightarrow-4\left(2m-1\right)=3\left(m+3\right)\\ \Leftrightarrow m=-\dfrac{5}{11}\left(tm\right)\)
\(\left(x+\dfrac{1}{2}\right)^2=1\)
\(\Leftrightarrow\left[{}\begin{matrix}x+\dfrac{1}{2}=1\\x+\dfrac{1}{2}=-1\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=\dfrac{1}{2}\\x=-\dfrac{3}{2}\end{matrix}\right.\)